THE EFFECT OF TEMPERATURE AND WATER CONDUCTIVITY IN HOT BASIN TOWARD EFFECTIVENESS OF COOLING TOWER ON UTILITY UNIT PT. X - Dhamayanthie, Indah; Mulyani, Yully (Faculty of Engineering, Universitas Swadaya Gunung Jati, 2023)
PT X is one of the Reviews largest ethanol producing plant in Indonesia, PT X located ± 15 km the northeast of Solo or 110 Km to the south of Central Java, SeAprilang. Cooling Tower is a tower or building of water circulation directly or indirectly contact with hot water and then converted into cold water expected that a number of heat from a fluid to another fluid. The Cooling Tower operates According to the diffusion principle, where temperature changes can result in a difference in the rate of temperature displacement. From the process in the cooling tower unit there are Several variables contained in the cooling towers ranging from the temperature and water conductivity in the hot basin. Obtained from the variables can be used to analyze the effectiveness of the cooling tower unit. When the conductivity contained in the water in the basin of hot high then the effectiveness of cooling tower will Decrease, likewise vice versa. And the value of effectiveness Obtained range of 76.12% - 87.80%. Where the company's standard value is 75% effectiveness. There are Several factors Determining the high value of conductivity values such as chemical mixing, high temperature in the cooling tower, and the temperature around the cooling tower.